Internet inquiry conversations about method - Markham, Annette N.; Baym, Nancy K.; Sage eBooks (London : SAGE, 2009)
'Internet Inquiry' takes readers into the minds of top Internet researchers as they discuss how they have worked through critical challenges as they research online social environments.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Internet research; Electronic books